Scaling-up the role of housewives peer group activists as an effective promotor in early detection and prevention of malnutrition - Sri Achadi Nugraheni; Apoina Kartini; Naila Fauziatin; Rizki Septia Saraswati; Niken Wening (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2022)
ABSTRAKLatar Belakang: Angka kejadian gizi buruk di Indonesia maupun di Provinsi Jawa Tengah dan Kota Semarang masih tinggi. Masalah tersebut disebabkan oleh kurangnya kesadaran dan pengetahuan terkait gizi di kalangan masyarakat, termasuk Aktivis Dasa Wisma. Salah satu alasan lainnya adalah kurangnya promotor gizi di tengah masyarakat, tokoh yang seharusnya berkaitan erat dengan kelompok sasaran, yaitu balita gizi buruk (stunting). Tujuan penelitian ini adalah melatih promotor gizi yang dapat melakukan deteksi dini dan pencegahan gizi buruk dengan baik dan efisien di tingkat Dasa Wisma sebagai upaya pencegahan stunting di tingkat masyarakat.Metode: Studi intervensi dengan rancangan kohort time series prospektif pada dua kelompok digunakan dalam penelitian ini. Tahapan kegiatannya adalah persiapan lapangan berupa Training of Trainer (TOT) bagi petugas gizi dan aktivis Dasa Wisma (66 aktivis terpilih), pengadaan sarana antropometrik penentuan status gizi, media, dan pelatihan bagi enumerator.Hasil: Aktivis Dasa Wisma yang dilatih mengalami peningkatan pengetahuan terkait gizi dan malnutrisi sebesar 2,66 poin (p<0,05) dan peningkatan keterampilan terkait pengukuran status gizi sebesar 0,68 poin (p<0,05).Kesimpulan: Peran Aktivis Dasa Wisma sangat penting untuk membantu ibu balita dalam melakukan pemantauan gizi anaknya; Selanjutnya, diharapkan semua ibu balita menyadari dan mempraktekkan keterampilan yang telah diperoleh untuk mencegah kejadian stunting sejak dini. KATA KUNCI: malnutrisi; stunting; pelatihan; Dasa Wisma; Promotor KesehatanABSTRACTBackground: The incidence of malnutrition in Indonesia especially in Central Java Province and in Semarang City is still high. The problem was due to lack of awareness and knowledge related to nutrition in the community, including Housewives Peer Group Activists. Another reason is due to the absence of nutrition promotors, persons who are closely related to the target group, under five children who were stunted. The objective of this study was to train efficient promotors in doing early detection and prevention of malnutrition at Housewives Peer Group Activists level as an effort to prevent stunting at the community level. Methods: An intervention study with a case control design in two groups used in this study. The stages of the activities were field preparation in the form of training of trainers (TOT) for nutrition officers and Housewives Peer Group Activists (66 activists selected), procurement of anthropometric infrastructure for determining nutritional status, media, and training for enumerator. Results: Housewives Peer Group Activists being trained had an increase in knowledge by 2.66 points (p <0.05) and an increase in skills related to measuring nutritional status by 0.68 points (p <0.05). Conclusion: The role of Housewives Peer Group Activists is very important in assisting mothers of children under five in conducting monitoring of their children’s nutrition; furthermore, it is hoped that all mothers of children under five realize and practice the skills they have acquired to prevent stunting.  KEYWORD: malnutrition; stunting; training; housewives peer group activist; health promotor